The 6th TECHNIUM International Conference: ISBN 978-606-95069-2-9 (PDF) - Nair, Sheeja (Technium Books, 2020)
The 6th TECHNIUM International Conference New decade on Social Sciences, Sustainable Future and Technology Development Session Coordinator: Assistant Professor Sheeja Nair Session Moderator: Dr. Raamani Thannimalai FIRST EDITION 2020 ISBN 978-606-95069-2-9 (PDF) Technium Books publish all content in open access, promoting the exchange of ideas and knowledge in a globalized world. Technium Books encompasses all the benefits of open access—high availability and visibility, as well as wide and rapid dissemination. Technium Books are distributed under the terms and conditions of the Creative Commons Attribution License — as an author, you retain the copyright for your work. Technium Books believes that the contemporary wave in academia of wider and faster dissemination of knowledge with open access should not be restricted to academic journals but should also capture and elevate academic & research book publishing. See visitor map: https://clustrmaps.com/site/1bg5q